Perbedaan Durasi Pneumonia pada Tipe-Tipe Penyakit Jantung Bawaan Asianotik Pirau Kiri ke Kanan - Masyithoh Wahyu Diani; Taufiq Hidayat; Rosi Amrilla Fagi (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2018)
Background: Acyanotic congenital heart disease with left to right shunt can increase blood flow to the lungs. It may cause respiratory tract infection. Acute respiratory tract infection, especially pneumonia, is the most common cause of mortality in children. Objective: To analyze the difference in duration of pneumonia in each types of acyanotic congenital heart disease with left-to-right shunts. Methods: This study was designed in cross-sectional. Subjects were children with acyanotic congenital heart disease, with left to right shunt, and pneumonia in the age of 1 month–5 years, who hospitalized in RSUD Dr. Soetomo, in the year of 2016. Results: Total subjects were 37 patients and 20 of them were boys. This case was mostly common in the patient under 12 months old (23 patients), had normal birthweight (15 patients), and had good nutrition (18 patients. Atrial Septal Defect (ASD) was the most common type lesion with pneumonia (35.14%). Duration of dyspnea was the longest (mean=7.43 days), while fever was the shortest (mean=2.27 days). Duration of cough was 7.06 days, while ronchi was 6.19 days. Patent Ductus Arteriosus (PDA) type lesion had the longest duration of pneumonia (mean=10.2 days). These findings suggest that there was no difference in duration of pneumonia in each types of acyanotic congenital heart disease with left-to-right shunts (p=0.371; p>?=0.05). Conclusion: There is no difference in duration of pneumonia in each types of acyanotic congenital heart disease with left-to-right shunts.